Do Smart Cities Technologies Contribute to Revenue Performance? Evidence from U.S. Local Governments. Issue 5 (3rd September 2022) - Nukpezah, Julius; Abutabenjeh, Sawsan; Azhar, Annus
Abstract: There is an increasing trend among local governments in the United States and elsewhere in the world to adopt smart cities technologies (SCT), but the question remains: Do these technologies contribute to government revenue performance? Drawing on the digital-era governance (DEG) literature for theoretical context, this article investigates the effects of commitment to, engagement with, and barriers encountered with SCT on government revenue performance. The effects are examined using performance data obtained from the 2016 International City/County Management Association (ICMA) Smart Cities Survey and the U.S. Census Bureau. The ordinary least squares (OLS) regression results provide empirical support to the assertion that higher engagement with SCT contributes to government revenue performance. Overall, we find that SCT contribute to local retail trade revenue collection efforts and health care and social assistance revenue of establishments in a local government area. The article offers policy implications on how local governments can improve their revenue performance using SCT that contribute to important public values such as timeliness, productivity, efficiency, effectiveness, and government competitiveness, as well as benevolence and human dignity.